Characterization of the Protective Efficacy Against QX Strain of a Recombinant Infectious Bronchitis Virus With H120 Backbone and QX Spike Gene - Weng, Wenlian; Liu, Qingyan; Xue, Wenxiang; Wang, Huan; Fang, Shouguo; Sun, Yingjie; Tan, Lei; Song, Cuiping; Qiu, Xusheng; Liu, Weiwei; Ding, Chan; Liao, Ying (Frontiers in Microbiology, 2022)
Infectious bronchitis virus (IBV) has been prevalent in chicken farm for many years, whose control relies on extensive vaccine administration. The continuous emergence of new variants and the low cross protection efficiency prompt the development of new vaccines. In this study, we develop a reverse genetics technique based on the classical vaccine strain H120 genome, via in vitro ligation method. Using H120 genome as backbone, we construct a recombinant virus rH120-QX(S) by replacing the H120 S gene with QX S gene, a prevalent strain in China. Biological characteristics of the rH120-QX (S) such as 50% egg lethal dose (ELD50), 50% egg infectious dose (EID50), dwarf embryo, growth curve, and genetic stability are measured, which are comparable to parental virus H120. There are no clinical symptoms and tissue lesions in trachea and kidney in rH120-QX(S)-infected specific-pathology-free (SPF) chickens, demonstrating this recombinant virus does not confer pathogenicity. Furthermore, protection studies show there is 100% homologous protection of rH120-QX(S) to virulent QX strain, as shown by the absence of clinical signs and no lethality. Taken together, our results demonstrate that swapping S gene onto H120 genetic backbone is a precise and effective way to produce genetically defined IBV vaccine candidate.